IMPLEMENTASI RESTFUL WEB SERVICE ONE CHIP MULTI-CLIENT UNTUK MENGOPTIMALKAN PENJUALAN PULSA ALL OPERATOR - Moh.Erwin Indrawan; Ahmat Adil (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2016)
Along with the development of information technology and telecommunications, evolving pulse function is not just used for SMS, telephone and internet, but also as a payment of transactions such as electricity prepaid, postpaid electricity, home phone, internet telecoms speedy, payments and other groceries. In credit sales, the chip can only be used by one agent, so it can not optimize the sales deposit balance both in terms of time, place and income because the chip can not be used by another person who made the sale of pulses is limited by time and place. Based on these problems, we need a resful architectural style web service as a liaison between the client and the server using the Java programming language, apache tomcat server and MySQL. The design of this application is done by using a waterfall methodology, which is a method of developing a system that begins with the analysis stage, then the system design, implementation and testing. With a system that can process one chip for all carriers from different places and platform, and also owners can optimize Wincell sales deposit both in terms of time, place and revenues